2000
DOI: 10.1063/1.126219
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage, 30 nm channel length, organic transistors with a self-assembled monolayer as gate insulating films

Abstract: We made nanometer-scale (gate length of 30 nm) organic thin-film transistors using a self-assembled monolayer (2 nm thick) as a gate insulator. The fabrication steps combine electron-beam lithography and lift-off techniques for the deposition of both metal electrodes and organic semiconductors with a chemical approach (self-assembly of organic molecules) to fabricate the gate insulator. Good performances of these transistors (with a record subthreshold slop of 350 mV/decade and a cutoff frequency of 20 kHz) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
190
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(195 citation statements)
references
References 15 publications
5
190
0
Order By: Relevance
“…[8][9][10] Later on, SAM dielectric films were indeed successfully employed for the fabrication of OTFT's by us [12] as well as by other groups. [13] In the present work, we demonstrate that these excellent tunnel dielectric behaviors are still valid down to 3 carbon atoms.…”
mentioning
confidence: 99%
“…[8][9][10] Later on, SAM dielectric films were indeed successfully employed for the fabrication of OTFT's by us [12] as well as by other groups. [13] In the present work, we demonstrate that these excellent tunnel dielectric behaviors are still valid down to 3 carbon atoms.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Collet et al, for example, used carboxyl terminated tetradecylenyltrichlorosilane SAMs on Si wafers for the fabrication of OFETs using evaporated ␣-sexithiophene. 11 Transistor operation at Ͻ2 V was demonstrated with gate leakage currents of ϳ10 −6 A / cm 2 . Other examples include work by Klauk et al 10,12 where they demonstrated low-voltage OFETs based on octadecylphosphonic acid ͑ODPA͒ SAMs as the gate dielectric employing evaporated organic semiconductors.…”
Section: Low-voltage Organic Transistors Based On Solution Processed mentioning
confidence: 99%
“…4 A number of efforts have achieved this target but typically at the cost of solution processability of the semiconductor/gate dielectric. [4][5][6][7][8][9][10][11][12][13] The primary advantage associated with solution processing is the simple fabrication and potentially lower manufacturing cost. However, controlling the morphology of solution processed films is usually complex and performance optimization is determined by many interrelated parameters, particularly wetting behavior of the semiconductor solution on the surface of the dielectric or substrate.…”
Section: Low-voltage Organic Transistors Based On Solution Processed mentioning
confidence: 99%
“…The monolayers have to withstand, without damage, a complete electron-beam patterning process for instance. This has been proved possible for SAMs of alkyl chains [76,77] and alkyl chain functionalized by π-conjugated oligomers [78] used in nano-scale (15 -100 nm) devices. However, recently developed soft-lithographies (micro-imprint contact…) can be used to pattern organic monolayers or to pattern electrodes on these monolayers [70].…”
Section: B At the "Device-like" Levelmentioning
confidence: 99%